Invasive squamous cell carcinoma of the conjunctiva - Sonda Kammoun; Mona Rekik; Saloua Ben Amor; Jamel Feki (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2020)
Introduction: Squamous cell carcinoma of the conjunctiva is generally a low-grade tumor. Invasive squamous cell carcinoma, however, is uncommon, and intraocular extension has rarely been reported. We report a case of invasive squamous cell carcinoma of the conjunctiva with intra-ocular involvement in 94 year-old man. Methods: A case report. Results: A 94-year-old male patient presented with a rapidly growing exophytic mass involving the right eyeball for 2 months.The biopsy performed a well differentiated squamous cell carcinoma of the conjunctiva.  The extension assessment showed local bone extension. The patient underwent exenteration with good postoperative consequences. Conclusion: This disease has a variable appearance. Late presentation with large orbital tumours are not uncommon. Early diagnosis is crucial to improve the visual prognosis.